A New Robust Watermarking Scheme to Increase Image Security. (20th October 2010) - Rahmani Rahmani, Hossein Hossein; Mortezaei Mortezaei, Reza Reza; Ebrahimi Moghaddam Ebrahimi Moghaddam, Mohsen Mohsen
Abstract : In digital image watermarking, an image is embedded into a picture for a variety of purposes such as captioning and copyright protection. In this paper, a robust private watermarking scheme for embedding a gray-scale watermark is proposed. In the proposed method, the watermark and original image are processed by applying blockwise DCT. Also, a Dynamic Fuzzy Inference System (DFIS) is used to identify the best place for watermark insertion by approximating the relationship established between the properties of HVS model. In the insertion phase, the DC coefficients of the original image are modified according to DC value of watermark and output of Fuzzy System. In the experiment phase, the CheckMark (StirMark MATLAB) software was used to verify the method robustness by applying several conventional attacks on the watermarked image. The results showed that the proposed scheme provided high image quality while it was robust against various attacks, such as Compression, Filtering, additive Noise, Cropping, Scaling, Changing aspect ratio, Copy attack, and Composite attack in comparison with related methods.